Revision of the subfamily Ostomopsinae (Coleoptera: Cerylonidae) - Jałoszyński, Paweł; Ślipiński, Adam (Zootaxa, 2021)
The subfamily Ostomopsinae of Cerylonidae is revised. Six nominal species are recognized and described or redescribed: Ostomopsis cudak sp. n. (Thailand), O. kuscheli sp. n. (New Caledonia), O. neotropicalis Lawrence & Stephan (USA: Florida; Mexico: San Luis Potosi, Veracruz; Panama, Cuba, Hispaniola, Jamaica, Guadeloupe, Montserrat), O. solitaria Scott (Seychelles, New Caledonia, Christmas Island, Northern Mariana Islands), O. solomon sp. n. (Solomon Islands), and O. watti sp. n. (New Caledonia). Morphological structures of the type species of Ostomopsis are illustrated and described in detail, and identification key to Ostomopsis species is given.